PENGARUH CITRA MEREK, KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN DI KFC KALIMALANG - Gilbert Rivaldo Rumimper; Rivera Pantro Sukma Silitonga (Human Capital Development, 2023)
The purpose of this research is to assess the influence of brand image and service quality on customer satisfaction through purchase decisions at KFC Kalimalang. The data was collected by distributing questionnaires to 114 respondents, using the purposive sampling method. Data analysis was carried out using SmartPLS. Service quality and brand image have a significant effect on purchasing decisions and customer satisfaction, but indirectly, through the mediation of purchasing decisions, no effect on customer satisfaction. Purchase decision has no significant effect on customer satisfaction